Enhancing Accessibility and Independence for the Visually Impaired: An Integrated QR Code-Based Shopping, Navigation, and Ticket Booking System - KC , Nithyasree; N, Palanivel; P, Vishnupriya; R, Akshaya; A, Anitha; S, Roshma (Journal of Neonatal Surgery, 2025)
The purpose of this project is to develop cutting-edge support systems that improve accessibility, independence and simple blinds through QR code product detection, real-time navigation systems, and voice-controlled ticket booking systems. I'm here. Founded on new language help, QR code scanning and GPS-based navigation technology, the system has established an improved shopping experience through the ability to scan product QR codes and listen to product names, brands and price information. Ta. The system also includes the "Add to Cart" feature, where users will arrange the desired elements and be aware of the total cost. This makes the shopping experience completely autonomous and knowledgeable without requesting instructions. and transit hubs. Using GPS and indoor positioning technology, the system allows visually impaired people to travel and travel with confidence in unknown areas without requesting external help. A comfortable, free booking experience is made possible by the system's ability to prevent visual interactions through text and text technology from language to text. This platform is easily accessible through the use of QR codes for product identification, ticket booking which enables straightforward purchases and independent purchases of navigation functions. These three new features will allow the target system to improve accessibility and independence from the visually impaired. A QR code-based product identification system allows for comfortable shopping, a navigation system improves travel mobility and reliability in new environments, and a ticket booking system guarantees easy access. This integrated auxiliary technology system not only improves the quality of life for blind users, but also contributes to the big goal of creating integrated, barrier-free public spaces through the dynamics of modern technology.